Development of technique for testing the long-term stability of silicon microstrip detectors - Kosinov, A.V.; Maslov, N. I.; Naumov, S. V.; Ovchinni, V. D.; Starodubtsev, A. F.; Vasilyev, G. P.; Yalovenko, V. I.; Bosisio, L. (Вопросы атомной науки и техники, 2006)
An automatic multi-channel set-up prototype for simultaneous testing of the Long-Term Stability (LTS)
*
of more
than ten detectors is described. The Inner Tracking System of the ALICE experiment will include about two thousand
Double-Sided Microstrip Detectors (DSMD). Efficient automatic measurement techniques are crucial for the
LTS test, because the corresponding test procedure should be performed on each detector and requires long times, at
least two days. By using special adapters for supporting and connecting the bare DSMDs, failing detectors can be
screened out before module assembly, thus minimizing the cost. Automated probe stations developed for a special
purpose or for microelectronics industry are used for measuring physical static DSMD characteristics and check
good-to-bad element ratio for DSMD. However, automated (or semi-automatic) test benches for studying LTS or
testing DSMD long-term stability before developing a detecting module are absent. Важная часть тестирования детектора и процедура определения гарантии качества состоит в изучении долговременной стабильности основных характеристик (ДСХ) детекторов, включая исследование эффектов влияния окружающей среды, таких как влажность или температура. В данной работе описаны метод тестирования и автоматический многоканальный стенд, специально разработанный для одновременного тестирования ДСХ более чем десяти детекторов Важлива частина тестування детектора і процедури визначення гарантії якості складається у вивченні
довгострокової стабільності основних характеристик (ДСХ) детекторів, включаючи дослідження ефектів
впливу навколишнього середовища, таких як вологість або температура. У даній роботі описані метод
тестування та автоматичний стенд, спеціально розроблений для одночасного тестування ДСХ більш ніж
десяти детекторів.